Randomised clinical trial for the cost–utility evaluation of two strategies of perineal reconstruction after abdominoperineal resection in the context of anorectal carcinoma: biological mesh repair versus primary perineal wound closure, study protocol for the GRECCAR 9 Study. Issue 4 (1st April 2021) - Buscail, Etienne; Canivet, Cindy; Ghouti, Laurent; Kirzin, Sylvain; Carrere, Nicolas; Molinier, Laurent; Rosillo, Aline; Lauwers-Cances, Valerie; Costa, Nadège
Abstract : Introduction: Abdominoperineal resections performed for anorectal tumours leave a large pelvic and perineal defect causing a high rate of morbidity of the perineal wound (40%–60%). Biological meshes offer possibilities for new standards of perineal wound reconstruction. Perineal fillings with biological mesh are expected to increase quality of life by reducing perineal morbidity. Methods and analysis: This is a multicentre, randomised and single-blinded study with a blinded endpoint evaluation, the experimental arm of which uses a biological mesh and the control arm of which is defined by the primary closure after abdominoperineal resection for cancer. Patients eligible for inclusion are patients with a proven history of rectal adenocarcinoma and anal canal epidermoid carcinoma for whom abdominoperineal resection was indicated after a multidisciplinary team discussion. All patients must have social security insurance or equivalent social protection. The main objective is to assess the incremental cost–utility ratio (ICUR) of two strategies of perineal closure after an abdominoperineal resection performed for anorectal cancer treatment: perineal filling with biological mesh versus primary perineal closure (70 patient in each arm). The secondary objectives focus on quality of life and morbidity data during a 1-year follow-up. Deterministic and probabilistic sensitivity analyses will be performed in order to estimate the uncertainty surrounding the ICUR. CIs will be constructed using the non-parametric bootstrap approach. A cost-effectiveness acceptability curve will be built so as to estimate the probability of efficiency of the biological meshes given a collective willingness-to-pay threshold. Ethics and dissemination: The study was approved by the Regional Ethical Review Board of 'Nord Ouest 1' (protocol reference number: 20.05.14.60714; national number: 2020-A01169-30). The results will be disseminated through conventional scientific channels. Trial registration number: ClinicalTrials.gov Registry (NCT02841293 ).